Different lysine-to-methionine ratios in a low-protein diet affect the microbiome and metabolome, influencing the jejunal barrier function in Tibetan sheep - Zhang, Fengshuo; Wu, Zhenling; Zhang, Yu; Su, Quyangangmao; Zhu, Kaina; Chen, Xuan; Hou, Shengzhen; Gui, Linsheng (Frontiers in Microbiology, 2025)
IntroductionThe objective of this study was to evaluate the effects of the dietary lysine (Lys)/ methionine (Met) ratio in a low-protein diet on short-chain fatty acid (SCFA) profiles, villus morphology, antioxidant capacity, and immune status of the jejunum in Tibetan sheep.MethodsA total of 90 weaned Tibetan sheep, each 2 months old with an initial weight of 15.37 ± 0.92 kg, were randomly divided into three treatment groups. These groups were supplemented with different Lys/Met ratios of 3 [low protein-high methionine (LP-H)], 2 [low protein-medium methionine (LP-M)], and 1 [low protein-low methionine (LP-L)] in the basal diet (10% crude protein). The feeding trial lasted 100 days, including a 10-day acclimation period and a 90-day experimental period.ResultsThe hematoxylin–eosin (H&E) sections showed that the LP-L group had a significantly increased villus height compared to the LP-M and LP-H groups (p < 0.05). In addition, the LP-L group showed higher levels of Superoxide dismutase (SOD) activity and Total Antioxidant Capacity (T-AOC) concentrations (p < 0.05). A lower concentration of Interleukin-1 beta (IL-1β) was observed in the LP-H group (p < 0.05). The activities of α-amylase, chymotrypsin, and lipase were higher in the LP-L group compared to the LP-H group (p < 0.05). Bacterial sequencing showed that both Chao1 and ACE richness were significantly increased in the LP-L group (p < 0.05), suggesting that the species richness in the jejunum is connected to the ratio of dietary Lys/Met. Furthermore, lowering the dietary Lys/ Met ratio significantly increased the abundance of Romboutsia, the Ruminococcus gauvreauii group, the Lachnospiraceae NK3A20 group, Ruminococcus 2, and the Christensenellaceae R-7 group (p < 0.05) while decreasing the abundance of Methanobrevibacter (p < 0.05). Several differential metabolites, including beta-alanine, pantothenate, pantothenic acid, phosphoenolpyruvate, cysteine, adenosine 5′-diphosphate, isodeoxycholic acid, glutamate conjugated cholic acid, and 3-dehydrocholic acid, were significantly increased in the LP-L group (p < 0.05). The functional analysis based on the Kyoto Encyclopedia of Genes and Genomes (KEGG) annotations indicated that these metabolites were mainly involved in pantothenate and CoA biosynthesis, ferroptosis, and the tricarboxylic acid cycle. Several genes related to barrier function, such as Occludin and Muc- 2, were upregulated in the LP-L group (p < 0.05), while IL-6 and TNF-α were downregulated (p < 0.05).DiscussionCollectively, our results suggest that the dietary Met/ Lys ratio could affect the jejunal SCFA concentration by modulating the microbial community and regulating metabolism, thereby contributing to jejunal barrier function. Our findings provide a theoretical basis for the application of Lys/Met diet supplementation in the nutritional management of Tibetan sheep, particularly when reducing the dietary crude protein (CP) level.